2023
DOI: 10.3390/microorganisms11020334
|View full text |Cite
|
Sign up to set email alerts
|

Weeds: An Insidious Enemy or a Tool to Boost Mycorrhization in Cropping Systems?

Abstract: Weeds have always been considered an insidious enemy, capable of reducing crop production. Conversely, the agroecological vision attributes a key role to the spontaneous flora in promoting plant diversity and belowground interactions, which may improve the ecological performance of agroecosystems. We summarized the literature on the weeds’ arbuscular–mycorrhizae (AM) interaction and we analyzed evidence on the: (i) AM suppressive/selective effect on weed communities; (ii) effect of weeds on AM colonization, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Several studies have reported greater colonization and AMF proliferation in soil under controlled agroecosystems in the presence of weeds [ 24 , 25 ]. However, under real field conditions, there is no information on how the presence of weeds impacts the crop root AMF community and soil AMF abundance, by considering both biotic and abiotic factors [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have reported greater colonization and AMF proliferation in soil under controlled agroecosystems in the presence of weeds [ 24 , 25 ]. However, under real field conditions, there is no information on how the presence of weeds impacts the crop root AMF community and soil AMF abundance, by considering both biotic and abiotic factors [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…More interestingly, the high AM propagule abundance produced in the soil in the presence of weeds had positive effects on the plant biomass and AM root colonization of M. sativa plantlets in pot culture in a greenhouse as shown by studies demonstrating the same patterns in controlled experiments [ 26 ]. It is also possible that these propagules are one of the factors responsible for the modifications in soil physico-chemical properties resulting in higher C and N contents in soil samples from blocks covered with wheat associated with weeds, as they are constituted and/or able to produce organic molecules such as chitin or glomalin, respectively [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These helpful microorganisms develop symbiotic relationships with a diverse variety of different horticultural crops, e.g., Ocimum basilicum , Lactuca sativa , Punica granatum , and S. lycopersicum [ 19 ]. AMF regulate plant growth and development by forming extra-radical mycelium around the roots, which are inaccessible to roots or even root hairs, enabling the interchange of nutrients and water for carbon sources such as sugars and lipids [ 20 , 21 ]. Plants inoculated with AMF, such as Festuca ovina , Opuntia ficus-indica , and Zea mays , enhance plant growth and improve the absorption of nutrients, especially nitrogen (N) and phosphorus (P), demonstrating the usefulness of AMF to various plant species [ 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [ 12 ] examined the effects of intercropping alfalfa with mulberry on the microbial community structures and physicochemical characteristics of soil, providing a framework for the optimal management of mulberry–alfalfa intercropping. While weeds are normally considered to be a nuisance in conventional monocropping agricultural production systems, Trinchera et al [ 13 ] ask us to consider an alternative perspective in summarizing the literature on the arbuscular mycorrhizal fungi associated with weedy species. Their “agroecological” vision recognizes the role of naturally occurring plants in enhancing plant and soil microbial diversity.…”
mentioning
confidence: 99%